2011
DOI: 10.1161/circulationaha.111.025270
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Worsens Diastolic Left Ventricular Dysfunction in Aortic Stenosis Through Altered Myocardial Structure and Cardiomyocyte Stiffness

Abstract: Background-Aortic stenosis (AS) and diabetes mellitus (DM) are frequent comorbidities in aging populations. In heart failure, DM worsens diastolic left ventricular (LV) dysfunction, thereby adversely affecting symptoms and prognosis. Effects of DM on diastolic LV function were therefore assessed in aortic stenosis, and underlying myocardial mechanisms were identified. Methods and Results-Patients referred for aortic valve replacement were subdivided into patients with AS and no DM (AS; nϭ46) and patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 203 publications
(172 citation statements)
references
References 47 publications
8
154
1
2
Order By: Relevance
“…An increased proportion of the compliant N2BA variants was observed in end-stage failing human hearts, including those from ischemic cardiomyopathy, 105 nonischemic DCM, 109,110 and other patients with HFrEF, 111 compared with nonfailing donor hearts (45%-50% versus ≈30%). In patients with aortic stenosis, the N2BA:N2B expression ratio was somewhat higher than in healthy control hearts in one study, 111 but unaltered 112 or reduced 113 in other studies. In the hearts of mice exposed to transverse aortic constriction, the N2BA:N2B ratio was significantly increased in comparison with healthy mouse hearts.…”
Section: Adjustment Of Titin Stiffness By Isoform Switching In Nonfaimentioning
confidence: 74%
See 2 more Smart Citations
“…An increased proportion of the compliant N2BA variants was observed in end-stage failing human hearts, including those from ischemic cardiomyopathy, 105 nonischemic DCM, 109,110 and other patients with HFrEF, 111 compared with nonfailing donor hearts (45%-50% versus ≈30%). In patients with aortic stenosis, the N2BA:N2B expression ratio was somewhat higher than in healthy control hearts in one study, 111 but unaltered 112 or reduced 113 in other studies. In the hearts of mice exposed to transverse aortic constriction, the N2BA:N2B ratio was significantly increased in comparison with healthy mouse hearts.…”
Section: Adjustment Of Titin Stiffness By Isoform Switching In Nonfaimentioning
confidence: 74%
“…117,125 A few studies have reported an increased ratio of phospho-N2BA:phospho-N2B in human HF, including HFpEF, aortic stenosis, and HFrEF. 111,112 However, as the N2BA:N2B isoform-expression ratio was also increased in these patient hearts, the proportion of phospho-titin to all-titin (per isoform) may have been similar in the nonfailing and failing hearts. Unaltered total-titin phosphorylation was recently found in end-stage failing DCM patients, compared with nonfailing donor hearts.…”
Section: Altered Titin Phosphorylation In Hf and Implications For Diamentioning
confidence: 88%
See 1 more Smart Citation
“…Aortic stenosis patients with diabetes mellitus, a frequent pathology in older patients, increases LV afterload and exhibits reduced LV distensibility compared to aortic stenosis patients without diabetes mellitus, indicating that disease complicated with comorbidities may result in more severe diastolic dysfunction (Paulus 2010;Paulus and Tschöpe 2013). Aortic stenosis with diabetes mellitus is associated with incre ased c ollagen volume fraction, increa sed intramyocardial vascular advanced glycation end product deposition, and high cardiomyocyte stiffness, in addition to titin hypophosphorylation (Falcão-Pires et al 2011;Borbély et al 2005;van Heerebeek et al 2006van Heerebeek et al , 2008Hamdani and Paulus 2011;Hamdani et al 2013aHamdani et al , b, 2014.…”
Section: •-mentioning
confidence: 99%
“…Myocardial fibrosis in DCM usually leads to ventricular diastole and contractile function disorders, and ultimately to congestive heart failure (14). Myocardial fibrosis is tightly linked to the high incidence and mortality associated with DCM.…”
Section: Introductionmentioning
confidence: 99%